Perbedaan Tekanan Darah Antara Shift Pagi, Sore, Malam Pada Perawat Rawat Inap Di Rumah Sakit Umum Daerah Banyudono - Rahmaningsih, Dias Puspita; , Tarwaka, PGDip Sc, M.Erg; , Kusuma Estu Werdani, SKM., M.Kes (2015)
Hospital provides health service for 24 hours that can not be separated from shift work system. Shift work cause the nurses work out from normal time. It will make the disturbance of human physiology, so that will influence of human blood pressure. The aim of this research is to show the blood pressure difference of nurses who work in the morning, afternoon and night shift at the RSUD Bayudono. This research method is analytic observational with cross sectional approach. The population of the research consist of 38 nurses who work in inpatient room at the RSUD Banyudono. Total sampling method was used to take sample. The data are taken from the respondent by measuring blood pressure in 3 times for every shift. Statistical testwith significant level (α=0,05) using Kruskal Wallis test, the result showed that there were significant differences of blood pressure in the morning, afternoon and night shift (p value = 0,026. Suggested to the nurses to keep the blood pressure in normal categories by doing exercise regularly.